Perspectives of women, healthcare providers and health managers on Group Antenatal Care implementation in Geita, Tanzania: A qualitative study - Alen Kinyina; Augustino Hellar; Raymond Bandio; Hamid Mandali; Ahmad Makuwani; Abubakari Munga; Phineas Sospeter; Yusuph Kulindwa; Ntuli Kapologwe; Frank Phiri; Isaac Lyatuu; Wilfred Kafuku; et al. (PLoS ONE, 2026)
Background Among the root causes of high maternal and neonatal mortality is low utilization of antenatal care (ANC) services and sub-optimal quality of care during pregnancy. Group Antenatal Care (G-ANC) is an innovative model of care where pregnant women with similar gestational age (GA) meet for their antenatal care visits as a group, rather than individually. This approach promotes peer support, shared learning, and a sense of community among pregnant women, and enhance the quality of care. This study aimed to assess the perspectives of healthcare providers (HCPs), women and health managers to determine the experience and acceptability of G-ANC in low resource settings. Methods The project was implemented from February 2023 to June 2024. However, participant recruitment for the qualitative component commenced in June to September 2024. Data was collected through six Focus Group Discussions (FGDs) with pregnant women and postnatal women who had recently attended G-ANC sessions. Key Informant Interviews (KIIs) were conducted with HCPs, facility leaders (in-charge) and district / regional health managers. Respondents were selected through purposive sampling, and discussions were conducted using semi-structured interview guides. Audio recorded interviews were transcribed, and thematic analysis was conducted using NVIVO software. Results Findings revealed positive experience, satisfaction and acceptability of G-among women and HCPs. Women reported increased knowledge on maternal health, emotional support, and enhanced communication with HCPs. Healthcare providers highlighted improved efficiency, better patient engagement, and peer support among clients. Health managers demonstrated contribution of G-ANC in promoting increased ANC attendance and more interactive care. However, challenges such as limited space, need for facilitator training, and resource constraints were identified. Conclusion Group Antenatal Care demonstrated significant benefits for maternal health education, peer support, and healthcare delivery efficiency. These findings add evidence to other existing literature supporting the adoption of this intervention in low resource settings. However, successful implementation requires investments in infrastructure (space for G-ANC meetings), adequate and trained HCPs, service integration and male engagement. Institutionalizing G-ANC as a standard antenatal care could be the best option to address the low coverage of ANC visits, suboptimal quality care, and promotion of institutional deliveries in low resource settings.